The Elusive History of the Pan-African Congress, 1919–27. (29th May 2021) - Hodder, Jake
Abstract: This paper considers the meetings of the interwar Pan-African Congress movement. It examines the Congress in the context of how conferencing became a dominant mode of international politics in the 1920s and the opportunities this offered to non-state actors. The Congress exemplified the hope which race reformers placed in the new international system established after the First World War, and in the League of Nations specifically. The paper considers three key conferencing elements in turn: delegates, venues, and resolutions. In each case, organizers mobilized the framework of conferencing to validate their political demands within this international system whilst, also in each case, their constrained circumstances required them to be strategically ambiguous with the facts of their meetings. As such, the paper encourages a broader methodological reflection on how historians approach seemingly unreliable historical sources. I argue that inconsistencies in reports of the Congress are themselves important historical artefacts of the political manoeuvres undertaken by race reformers. Foregrounding these strategies allows us to consider how political authority was circumscribed in the past, the resourcefulness of those on the political margins, and the promise and failure of international governance on the race question in the 1920s.